Stress and depression in university health students - Julia Zancan Bresolin; Graziele de Lima Dalmolin; Silvio José Lemos Vasconcellos; Rafaela Andolhe; Bruna Xavier Morais; Taís Carpes Lanes (Rev Rene)
Objective: to analyze the association between stress and depression in university health students. Methods: cross-sectional study conducted with 792 university health students. The research instrument consisted of characterization of the students, Beck Depression Inventory version II and the Perceived Stress Scale. Absolute and relative frequency analysis, mean, standard deviation, median, interquartile range, and analytical statistics were used. Results: an association between depression and stress was observed (p<0.001) as well as a strong correlation between them (r=0.731; p<0.001). In high level of stress 9.5% of the students were found and in moderate to severe intensity of common symptoms of depression, 23.6% of them. Conclusion: a difference was noticed in the averages between the levels of depression and stress, in that the higher the level of depression, the higher the average stress. Contributions to practice: stress is related to depression in university health students, who, after graduation, may enter the labor market already sick, which brings implications for interpersonal relationships, worker health and patient safety. This enables higher education institutions to reflect on the organization of practices and intervention policies for the reduction of stress and depression among students.